Literacy in the English-speaking Caribbean : some responses to the problems of illiteracy and functional illiteracy. - Ellis, Patricia (1990)
Examines programmes and projects undertaken by government and non-governmental institutions at the national and regional levels to address the inadequate literacy levels. Highlights issues that must be looked at if progress is to be made toward the goal of eradication of illiteracy by the 21st century.